The symbolic cartoon: critical thinking forming tool - Medina Rincón, Lina María; Villamarín Ferro, Natalia (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Critical thinking is today a pressing need in pedagogical environments. Awaken in our students a critical-reflective attitude and, at the same time, we engage inpurposeful changes in educational practices. The image as an effective tool in communication processes, allows the potentializing of the creative and reflective subject. Thus, the symbolic caricature is proposed as a tool to encourage interpretation strategies. The research group, implemented activities in first and eleventh grade students of the Educational Institution “Álvaro González Santana”, pointing to pedagogical practices that develop critical thinking. This new way of assuming thought through the appreciation of the work of the cartoonists “Matador” and “Goyo”, projects situations in which the semiotic and metaphoric function are pluralized. Methodologically, it is based on direct observation, workshops and field journals, which result in the improvement of critical thinking skills.